2009
DOI: 10.11144/javeriana.sc14-2-3.cmdm
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización molecular de materiales cultivados de gulupa (Passiflora edulis f. edulis)

Abstract: Comunicación corta Facultad de Ciencias Resumen Objetivo. Caracterizar mediante marcadores moleculares RAM (Random Amplified Microsatellite) la diversidad genética de materiales cultivados de gulupa (Passiflora edulis f. edulis), colectados en los departamentos de Boyacá, Cundinamarca y Huila. Materiales y métodos. Hojas jóvenes y en buen estado fitosanitario fueron colectadas en fincas productoras de gulupa, para la extracción de ADN y caracterización mediante marcadores moleculares RAM, de acuerdo con el pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(3 reference statements)
0
3
0
3
Order By: Relevance
“…The only exception is accession “Gulupa” from Colombia. This accession, however, is believed to have been originally collected in Brazil and later introduced in Colombia [ 47 , 48 ] and was, therefore, also used in the analysis. These ten P. edulis accessions were genotyped with a random sample of 60 di- and tri-nucleotide microsatellites.…”
Section: Methodsmentioning
confidence: 99%
“…The only exception is accession “Gulupa” from Colombia. This accession, however, is believed to have been originally collected in Brazil and later introduced in Colombia [ 47 , 48 ] and was, therefore, also used in the analysis. These ten P. edulis accessions were genotyped with a random sample of 60 di- and tri-nucleotide microsatellites.…”
Section: Methodsmentioning
confidence: 99%
“…In Colombia, genetic diversity studies on Passiflora, such as those carried out by Fonseca-Trujillo et al (2009), who used ISSR markers, have characterized the cultivated gulupa materials collected in the Departments of Boyacá, Cundinamarca and Huila, finding that these molecular markers were efficient at detecting polymorphisms in this species (89%), evidencing broad genetic diversity that is distributed in the areas where gulupa is grown. The gulupa materials evaluated in this study showed high genetic diversity, probably because of the propagation method, origin and short time of establishment of these crops in this country.…”
Section: Meneses Et Al 2019)mentioning
confidence: 99%
“…La caracterización a través marcadores moleculares es una herramienta valiosa que tiene varias ventajas, como su independencia del medio ambiente y el alto nivel de polimorfismo que se puede encontrar distribuido por el genoma (Fonseca-Trujillo et al, 2009). Los microsatélites o SSR's, secuencias simples de ADN con motivos de 1 a 6 nucleótidos repetidos en tándem, se usan como marcadores y poseen características útiles para estudiar la diversidad genética de una población.…”
Section: Introductionunclassified